Dlaczego one chodzą do kościoła. Komedia w jednym akcie [przełożyła i opracowała Joanna Raźny] - Roussel, Nelly (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The translation of a one-act comedy Pourquoi elles vont á l’église is the first time when a work by Nelly Roussel is presented in Polish. Nelly Roussel ( 1878–1922) was a French free-thinker, feminist and anarchist, a representative of the ‘Combat Theater’ movement (théâtre de combat), a precursor of feminist drama the message of which — introduced in times of Third Republic — will be undertaken by emancipation movements of the 1960s and the 1970s. The first edition of the play appeared in Paris without the date of issue on the front page, around 1903. This translation was based on an issue of Au temps de l’anarchie. Un théâtre de combat.1880-1914. Textes choisis, établis et présentés par Jonny Ebstein, Philippe Ivernel, Monique Surel-Tupin et Sylvie Thomas; préface d’Alain Badiou. Biarritz (Pyrénnées-Atlantiques): Séquier/Archimbaud, 2001. T. 1, p. 359–372. All text annotations by the translator.